Ameliorated membranous nephropathy activities of two ethanol extracts from corn silk and identification of flavonoid active compounds by LC-MS2. Issue 20 (20th August 2021) - Wang, Xizhu; Yuan, Liyan; Dong, Yifei; Bao, Zhijie; Ma, Tiecheng; Lin, Songyi
Abstract : We speculate that the ameliorated MN activity of corn silk relates mainly to PR-CSEE and the synergistic action of the 12 flavonoid components therein, and that apigenin and its derivatives may play a major role. Abstract : The current study looks to evaluate the effect of corn silk flavonoids on membranous nephropathy (MN). Polyamide resin (PR) can be used to enrich corn silk ethanol extract (CSEE) to obtain flavonoid-rich extract (PR-CSEE), the total flavonoid content (TFC) of which we found to be 57.4%. The results of scanning electron microscope, Fourier-transform infrared, and high-performance liquid chromatography analyses determined that PR-CSEE and CSEE have different structural characteristics, but that PR-CSEE has higher TFC. MN mice models were induced by cationic bovine serum albumin, and we found that PR-CSEE administration reduced urine protein levels markedly, while renal function, glomerular atrophy, inflammatory infiltration, and in-serum immunoglobulin G and complement 3 content were improved. Through LC-MS 2 spectrometry analysis, we pinpointed the 12 major flavonoid active compounds in PR-CSEE. These findings suggest that PR-CSEE can act as a potential functional food material by which to improve MN.